Análise geoespacial da ocorrência de dengue no período de 2016 á 2018 no município de Ananindeua – PA - CORRÊA, Devid Sivaldo da Silva (2019)
The objective of this work was to use the geographic information systems (GIS) for the spatial analysis of dengue occurrence in the municipality of Ananindeua-Pará from 2016 to 2018, being relevant the perception of basic sanitation, environmental and political issues to make georeferencing effective in promoting health. The objective of this study was to identify which factors contribute to the occurrence of dengue in the municipality, and generate knowledge to apply the best possible public policies that already exist and those that still must exist. Therefore, a quantitative research was conducted to verify the spatial distribution of dengue cases in the municipality, based on the confirmed cases of the Municipal Health Department of Ananindeua (SESAU). Software such as QGIS and Excel were used to make the maps and graphs, statistical correlations were established between the variables. It was possible to observe that in the three years of research the distribution of dengue occurred largely in the first half of 2016, which coincides with the rainy season, which allied with the neglect of public management with garbage, becomes a perfect match for the proliferation of the Aedes mosquito. The year 2016 presented a high number of occurrences and in the following year there was a decrease of the cases as the cause gained innovative reinforcement of the company supplying energy to combat the mosquito. However, in 2018 the neglect was again presented in the environmental issue, generating an increase in cases. It was concluded that geoprocessing proved to be an important tool to guide decision-making in the fight against dengue vectors in the municipality of Ananindeua, since with the spatialization of the cases, it was possible to have a better diagnosis to identify the foci.